Vertical knowledge transfer in Czech organizations - Urbancová, Hana; Fejfarová, Martina (Business: Theory and Practice, 2015)
For organizations the losing key employees is the greatest threat; if the organizations lose the key workers, they cannot use their premises, data, information and other resources. The article aims at evaluation of the level of vertical knowledge transfer in organizations in the Czech Republic. The partial goals of this article are to determine dependencies between the examined qualitative features. The article has been drawn up using scientific methods, in particular logical methods, such as analysis, synthesis, induction, deduction and comparison. The results were obtained from longitudinal quantitative research in organizations in the Czech Republic from 2010 to 2014. The article identifies the factors affecting vertical knowledge transfer and presents a method of eliminating the risk of losing key knowledge workers. Vertical knowledge transfer is a new supporting factor of organizations’ productivity and business continuity.